(untitled) (International Journal of Food and Nutritional Sciences, 2021)
There is a lot of business done these days, especially business involving land. For the great majority of these transactions, conventional database systems are the basis. A centralised system like the database makes it vulnerable. The records can be updated because database systems’ data is modifiable. Building a property record using block chain technology may be a preferable solution. Immutable data can only be found in the block chain. After it has been completed, a block chain transaction cannot be altered. The transactions are more secure thanks to a block chain network’s immutability. A block chain provides the security and accuracy of a data record without the need of a trustworthy third party.